Perpendicularly magnetized Co/Pd-based magneto-resistive heterostructures on flexible substrates. Issue 11 (16th April 2021) - Hassan, M.; Laureti, S.; Rinaldi, C.; Fagiani, F.; Varotto, S.; Barucca, G.; Schmidt, N. Y.; Varvaro, G.; Albrecht, M.
Abstract : Flexible PMA spin-valve thin film stacks with a high magneto-electric robustness aginst bending were obtained on large-area substrates by using an effective and versatile Au-mediated transfer and bonding strategy. Abstract : Flexible magneto-resistive heterostructures have received a great deal of attention over the past few years as they allow for new product paradigms that are not possible with conventional rigid substrates. While the progress and development of systems with longitudinal magnetic anisotropy on non-planar substrates has been remarkable, flexible magneto-resistive heterostructures with perpendicular magnetic anisotropy (PMA) have never been studied despite the possibility to obtain additional functionality and improved performance. To fill this gap, flexible PMA Co/Pd-based giant magneto-resistive (GMR) spin-valve stacks were prepared by using an innovative transfer-and-bonding strategy exploiting the low adhesion of a gold underlayer to SiO x /Si(100) substrates. The approach allows overcoming the limits of the direct deposition on commonly used polymer substrates, whose high surface roughness and low melting temperature could hinder the growth of complex heterostructures with perpendicular magnetic anisotropy. The obtained PMA flexible spin-valves show a sizeable GMR ratio (∼1.5%), which is not affected by the transfer process, and a high robustness against bending as indicated by the slight change of the magneto-resistive properties upon bending, thus allowing for their integration on curved surfaces and the development of a novel class of advanced devices based on flexible magneto-resistive structures with perpendicular magnetic anisotropy. Besides endowing the family of flexible electronics with PMA magneto-resistive heterostructures, the exploitation of the results might apply to high temperature growth processes and to the fabrication of other functional and flexible multilayer materials engineered at the nanoscale.